INTERNALIZATION OF THE PANCASILA STUDENT PROFILE IN SHAPING THE CHARACTER OF CLASS VA STUDENTS AT UPTD SD INPRES LILIBA KUPANG CITY - Windyantri M Lado; Yulsy M. Nitte; Cornelia A. Naitili (Universitas Citra Bangsa, 2025)
This research aims to describe the internalization of the Pancasila Student Profile in shaping the character of Class VA students at UPTD SD Inpres Liliba, Kupang City. The research method used is qualitative descriptive. The research focuses on the application of six dimensions of the Pancasila Student Profile: faith and devotion to the Almighty God along with noble character, global diversity, cooperation, independence, critical reasoning, and creativity. Data collection techniques included interviews, observations, and documentation. Primary data were obtained from respondents, while secondary data were sourced from theories, journals, and related school documents. The research concluded that character values based on the Pancasila Student Profile have been successfully internalized in shaping the character of Class VA students at UPTD SD Inpres Liliba, Kupang City. This was achieved through the implementation of Pancasila values in curricular, extracurricular, and school cultural activities. Despite challenges such as limited teacher understanding, lack of facilities, and minimal collaboration with parents, efforts like teacher training, the use of learning media, and cooperation with parents effectively improved the internalization of Pancasila values. As a result, students demonstrated character traits aligned with Pancasila values, such as cooperation and independence. This initiative aims to create a generation with strong character aligned with Pancasila values.